Temporality in Badiou’s Ontology and Greater Logic - Ličer, Matjaž (Filozofski vestnik, 2022)
In his ontology, Badiou operates with historical situations that are identified as situations whose representation regime is prone to change. Similarly, his Greater Logic operates with changes and modifications of the transcendental related to a change in a particular world determined by its transcendental. In both ontology and logic, Badiou often loosely relates the occurrence of change to temporality, but the operative concept of temporality remains unclear. The paper aims to provide a concept of temporality, borrowed from physics, and which seems consistent with Badiou’s system of thought and helps in comprehending it. We use this concept of time, which explicitly links disorder and temporality (or lack of temporality) in an attempt to elucidate certain parts of Badiou’s ontology and logic.